2021
DOI: 10.3390/pharmacy9010050
|View full text |Cite
|
Sign up to set email alerts
|

The Subjective Experience of Using Medications: What We Know and the Paths Forward

Abstract: Medications can cause bodily changes, where the associated benefits and risks are carefully assessed based on the changes experienced in the phenomenal body. For this reason, the phenomenology of Merleau-Ponty is an important theoretical framework for the study of experience related to the daily use of medications. The aim of this study was to discuss the contribution of a recently developed framework of the general ways people can experience the daily use of medications—resolution, adversity, ambiguity, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The present study demonstrated that for chronically HCV-infected patients utilizing the second-generation DAAs; this experience represented the resolution of the virus-related whole-body issues, i.e., a solution to a disturbance in the phenomenal body [29,30]. Several studies have indicated that the presence of the virus directs one's gaze to the physical body, as a contaminated body [16][17][18][19].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The present study demonstrated that for chronically HCV-infected patients utilizing the second-generation DAAs; this experience represented the resolution of the virus-related whole-body issues, i.e., a solution to a disturbance in the phenomenal body [29,30]. Several studies have indicated that the presence of the virus directs one's gaze to the physical body, as a contaminated body [16][17][18][19].…”
Section: Discussionmentioning
confidence: 55%
“…However, being aware of the difficulties experienced by patients is not enough to guide reflective practice [28]. It is also important to operationalize knowledge related to the experience of using medications and this application in clinical care should not be overlooked [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…5 This often involves the person adopting new routines, behaviors, or skills that are often underappreciated by healthcare providers, some of which may not fit well with the person's life and goals. [28][29][30] Thus, providers must pay attention to these aspects of a person's medication experience in light of PGx information, rather than just whether or not patients are taking their medications. A similar approach can be incorporated with adherence measures, which are most often indirect measures like pill counts, claims databases, and self-reported questionnaires, to improve both the fidelity and explanatory value of this information.…”
Section: Care Quality Metricsmentioning
confidence: 99%
“…The OTPF-4 defines medication management as “communicating with the physician about prescriptions, filling prescriptions at the pharmacy, interpreting medication instructions, taking medications on a routine basis, and refilling prescriptions in a timely manner” (AOTA, 2020, p. 32). It is common for adults with MCCs to face adversities in managing multiple medications (Nascimento & Ramalho-de-Oliveira, 2021), making medication management an essential and complex occupation for this population (Eriksen et al, 2020; Leland et al, 2017; Mohammed et al, 2016). Medication-related complexities are of considerable concern because they often contribute to adverse health outcomes and diminished well-being (Cheng et al, 2019; Mohammed et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Medication management has an emerging voice in the OT literature, where it is framed from a generic or minimally contextualized medication adherence perspective rooted in the biomedical model, focused primarily on task and routine performance and based on knowledge generated from the pharmacy literature (AOTA, 2020; Sanders & Van Oss, 2013; Seibert & Schwartz, 2017). A limitation of this perspective is the primary focus on individual responsibility and minimization of the impact of complexities such as systemic issues, burdens, and power differentials on health outcomes (James et al, 2022; Nascimento & Ramalho-de-Oliveira, 2021; Rathbone et al, 2021; Talero, 2020). These complexities can contribute to the low to moderate effectiveness of varied behavioral and educational interventions designed to improve medication-taking and adherence behaviors (Conn & Ruppar, 2017; Cross et al, 2020).…”
Section: Introductionmentioning
confidence: 99%